Thermal analysis of adsorptive natural gas storages during dynamic charge phase at room temperature - Ridha, Firas Noori; Yunus, Rosli M.; Rashid, Mohd.; Ismail, Ahmad Fauzi (Elsevier Inc., 2007)

(untitled)
The thermal behavior of an adsorptive natural gas (ANG) vessel pressurized continuously with light hydrocarbon gases and their mixture at 27 °C was analyzed using two different activated carbons. Activated carbon AC-L showed better isothermal storage capacity than AC-D due to its sufficient porous structure. However, higher adsorption capacity claimed more extreme thermal fluctuation represented by a temperature rise of 99.2 °C at the center region of the bed charged continuously with methane at 1 L min−1 up to pressure of 4 MPa, corresponding to 82.5 °C in AC-D bed. Higher charge rate of 5 L min−1 claimed severer thermal fluctuation of 116 °C in AC-L/methane system calling for a serious reduction of 26.9% in the dynamic storage capacity with respect to the isothermal storage capacity. This reduction brought the storage system to a working pressure of about 2.5 MPa rather than the desired working pressure of 4 MPa (about 40% reduction in storage pressure). The severest temperature rise was at the center region caused by bed poor thermal conductivity leading to limited heat transfer. High ethane and propane portions in natural gas may contribute to the thermal fluctuation of the storage system as their heats of adsorption are higher than that for methane